2019
DOI: 10.1016/s1473-3099(18)30755-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with revision for prosthetic joint infection following knee replacement: an observational cohort study from England and Wales

Abstract: Background Prosthetic joint infection is a devastating complication of knee replacement. The risk of developing a prosthetic joint infection is affected by patient, surgical, and health-care system factors. Existing evidence is limited by heterogeneity in populations studied, short follow-up, inadequate power, and does not differentiate early prosthetic joint infection, most likely related to the intervention, from late infection, more likely to occur due to haematogenous bacterial spread. We aimed to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
167
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(183 citation statements)
references
References 34 publications
12
167
1
3
Order By: Relevance
“…We found that at tropical sites, patients with positive swabs following surgery were more likely to be younger, male, had undergone knee surgery and have had primary procedures. Age and gender have been well described in the literature as risk factors for infection following orthopaedic surgery, and it is also known from national joint replacement registry data that knee replacements pose a higher risk than for hips [27][28][29][30]. We note that both subtropical sites included in our study are located within the same metropolitan city, while the four tropical sites are regional and remote with substantially lower population densities.…”
Section: Discussionmentioning
confidence: 60%
“…We found that at tropical sites, patients with positive swabs following surgery were more likely to be younger, male, had undergone knee surgery and have had primary procedures. Age and gender have been well described in the literature as risk factors for infection following orthopaedic surgery, and it is also known from national joint replacement registry data that knee replacements pose a higher risk than for hips [27][28][29][30]. We note that both subtropical sites included in our study are located within the same metropolitan city, while the four tropical sites are regional and remote with substantially lower population densities.…”
Section: Discussionmentioning
confidence: 60%
“…При эндопротезированиии коленного сустава тип имплантата в целом не рассматривается как фактор риска ППИ. Последний метаанализ 2019 г. показал, что риск ППИ при эндопротезировании коленного сустава меньше при бесцементном, одномыщелковом и пателлофеморальном эндопротезах [9], выбор которых больше определяется клинической ситуацией, и влиять на этот фактор риска затруднительно.…”
Section: требования по мониторингу безопасности имплантатов: россия иunclassified
“…Many studies have attempted to identify potential risk factors for PJI. For example, individuals with a medical history of an inflammatory disease have been shown to be independently associated with more than 4 times as many subsequent PJIs than those with osteoarthritis due to the long-term use of disease-modifying antirheumatic drugs (DMARDs) [11], biological drugs and corticosteroids [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%